2021
DOI: 10.3390/agronomy11050969
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Relevance of Soil Compaction and Application of Measures to Prevent It among German Farmers

Abstract: Intensive field traffic and high axle loads can lead to soil compaction, with ecological and economic consequences. However, the relevance of this issue among practitioners is largely unknown. Therefore, the aim of this study was to determine the relevance of this issue for farmers in Germany, whether and which mitigation measures are applied to avoid it, and what a (non-) application might depend on. We conducted an online survey among farmers in Germany in winter 2017/2018. For the majority of the respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Bulk density was negatively correlated with soil porosity (r = -0.842; P-value = 0.000; N = 18). Soil compaction causes a decrease in porosity value, which will interfere with water distribution into the soil (Ledermüller et al, 2021). Bachtiar (2019) found that the lower the bulk density, the more the total pore volume of the soil increases, and Sudaryono (2001) revealed the same thing.…”
Section: Land Usementioning
confidence: 99%
“…Bulk density was negatively correlated with soil porosity (r = -0.842; P-value = 0.000; N = 18). Soil compaction causes a decrease in porosity value, which will interfere with water distribution into the soil (Ledermüller et al, 2021). Bachtiar (2019) found that the lower the bulk density, the more the total pore volume of the soil increases, and Sudaryono (2001) revealed the same thing.…”
Section: Land Usementioning
confidence: 99%
“…Soil compaction is a common worldwide problem affecting many crop growing areas (Shaheb et al, 2021;Ledermüller et al, 2021). Soil compaction negatively affects plant growth and development.…”
mentioning
confidence: 99%
“…This increased attention is especially related to the impacts of the increasing mechanization and wheel loads of machines in agriculture (Keller et al, 2019b). It was noted that a significant fraction of arable farmers in Germany are aware of the risk of intensive field traffic and high axle loads for subsoil compaction, but that this awareness had not yet led to adequate changes in practice (Ledermüller et al, 2021). Indeed, impacts of human-induced (sub)soil compaction seem to increase over time (Antille et al, 2019;Soane and Van Ouwerkerk, 1995;Sonderegger and Pfister, 2021).…”
Section: Introductionmentioning
confidence: 99%